Contribution to the study of Maize and Maize Chicha - Velasquez, Manuel A. (1919)
It is not our purpose to write the history of maize and chicha in America study would require a huge extension and which should preferably be: the botanical origin of maize; the importance of corn in ancient American peoples; different species of the genus Zea; varieties from Zea mays L. grown in the country and its chemical composition; how to make chicha corn throughout the Peruvian territory and chemical composition of it, etc. etc. We will not make it a concise history of maize and study the preparation and chemical composition of some Peruvian chicha, the most renowned.